Capture of [Bi4]6− and [Bi3]5− anions by [Rh(L)]+ (L = COD) cations in the closo heteroatomic clusters {Bi4[Rh(L)]4}2− and {Bi3[Rh(L)]3}2−. (1st February 2023) - Liang, Zhibing; Lin, Lifang; Liang, Yuanwei; Wang, Yi
Abstract : Two closo hybrid polybismuthides {Bi4 [Rh(COD)]4 } 2− (1 ) and {Bi3 [Rh(COD)]3 } 2− (2 ), derived respectively from the unprecedented envelop-like [Bi4 ] 6− and V-type [Bi3 ] 5− anions by the coordination of the [Rh(COD)] + cation units, were fully characterized. Abstract : Compared with the rich chemistry of the lighter polypnictides [Pn x ] q − (Pn = P, As, Sb, q = charge), our knowledge about the polybismuthides [Bi x ] q − is still very limited. Here we report two transition metal polybismuthides {Bi4 [Rh(COD)]4 } 2− (1 ) and {Bi3 [Rh(COD)]3 } 2− (2 ), which were isolated by the reaction of the K5 Bi4 /ethylenediamine(en) solutions with 18-crown-6/Rh(COD)(acac) (COD = 1, 5-cyclooctadiene, acac = acetylacetonate) and 2, 2, 2-crypt/Rh(COD)(Cp) (Cp = cyclopentadiene), respectively. Cluster anions 1 and 2 could be viewed as complexes generated from the capture of envelope-like [Bi4 ] 6− and V-type [Bi3 ] 5− anions by the [Rh(COD)] + cation units. Both 1 and 2 are closo (2 n + 2) deltahedral structures and have been systematically characterized by single crystal X-ray diffraction (SXRD), energy dispersive X-ray spectroscopy (EDX), electrospray ionization mass spectroscopy (ESI-MS) and NMR ( 1 H and 13 C). These findings underline an efficient route to the isolation of novel Zintl anions that are otherwise inaccessible by the introduction of ligated transition metals.